Peningkatan Kemampuan Berhitung Anak melalui Permainan Gelas Hitung di PAUD - Waty, Sri Diam Eka; Saridewi, Saridewi (Penerbit Aksara Rentaka Siar (ARS), 2019)
Children arithmetic in PAUD Tunas Bangsa distric Nanggalo Padang still low. The goal is to increase the ability of counting children. This type of research is the study of the subject with the class action researcher is the group A1. This research was conducted with two cycles i.e. cycles I held 3 times and cycles II results when you have reached the of complete a minimum. Thus it can be concluded that with the glass count game can increase the ability of counting children in district Nanggalo Padang.